2010
DOI: 10.1002/prca.200900145
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of bacterial pathogenicity: Therapeutic implications

Abstract: Identification of the molecular mechanisms of host-pathogen interaction is becoming a key focus of proteomics. Analysis of these interactions holds promise for significant developments in the identification of new therapeutic strategies to combat infectious diseases, a process that will also benefit parallel improvements in molecular diagnostics, biomarker identification and drug discovery. This review highlights recent advances in functional proteomics initiatives in infectious disease with emphasis on studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 160 publications
1
9
0
Order By: Relevance
“…2, if the scope of reference is expanded to include proteins identified in published studies that comprehensively profile membrane, cell wall, and secreted proteins of M. marinum, M. avium subsp. paratuberculosis, and M. tuberculosis, the results indicate that ϳ90% of the proteins detected in this study are close homologues of proteins previously identified as plasma membrane, secreted, and/or cell wall-associated mycobacterial proteins (30,32,51,54,84,87) (see Table S1 in the supplemental material).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…2, if the scope of reference is expanded to include proteins identified in published studies that comprehensively profile membrane, cell wall, and secreted proteins of M. marinum, M. avium subsp. paratuberculosis, and M. tuberculosis, the results indicate that ϳ90% of the proteins detected in this study are close homologues of proteins previously identified as plasma membrane, secreted, and/or cell wall-associated mycobacterial proteins (30,32,51,54,84,87) (see Table S1 in the supplemental material).…”
Section: Resultssupporting
confidence: 72%
“…While previous studies have identified many of the cell membrane, cell wall, and surface-exposed proteins of related mycobacteria (30,32,51,54,74,84,87), little is known specifically about the surface-exposed proteome of M. avium subsp. hominissuis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations